2014
DOI: 10.22260/isarc2014/0079
|View full text |Cite
|
Sign up to set email alerts
|

Application of Building Information Modeling in Designing Fire Evacuation – a Case Study

Abstract: -In recent years, the construction industry has been actively seeking for possible applications of Building Information Modeling (BIM), including the domain of building disaster-prevention management. BIM enables us to present a facility layout in threedimension (3D) and carry the disaster-prevention objects and information whereas the traditional approach can only be presented in two-dimension. Therefore, it could be possible to improve the traditional two-dimensional (2D) plane of building disaster-preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…A safe evacuation plan for human is very crucial during fire accidents. BIM-based disaster prevention management system was developed by offering built-in functions such as escape route planning, training, and maintenance record keeping feature for fire safety equipment [17]. In order to understand human behavior during burning tragedies and evacuation, a BIM-based serious human rescue game simulation method was proposed [28].…”
Section: Current Fire Safety Management Status In Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…A safe evacuation plan for human is very crucial during fire accidents. BIM-based disaster prevention management system was developed by offering built-in functions such as escape route planning, training, and maintenance record keeping feature for fire safety equipment [17]. In order to understand human behavior during burning tragedies and evacuation, a BIM-based serious human rescue game simulation method was proposed [28].…”
Section: Current Fire Safety Management Status In Constructionmentioning
confidence: 99%
“…On the contrary, some studies have focused on the BIM application in the design for fire evacuation assessment [17], equipment maintenance, escape route planning, and safety education [16]. However, there is a lake of integration for firefighting equipment installation planning and its integration with fire safety management.…”
Section: Construction Safety Planning and Fire Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, new tools and techniques have been developed over the recent decade to meet with the required fire safety rule compliance. Several concepts and their enabling technologies have been investigated to attain enhanced fire safety management [17], [25]- [28], though automated rule-based fire safety planning for PFE placement is not yet achieved. Traditionally, essential inspection information related to firefighting equipment is primarily distributed among the stakeholders; however, this can occasionally lead to data loss [25].…”
Section: Literature Review a Limitations Of The Current Fire Safmentioning
confidence: 99%
“…The Model of Game-based Learning in Fire Safety was developed based on the combination of Game-Based Learning Model [22], Fire Safety Model [27] and the user requirements obtained from the preliminary study as shown in Fig. 3.…”
Section: B Model Of Game-based Learning In Fire Safety (Design Phase)mentioning
confidence: 99%